Drug‐Loaded Multifunctional Nanoparticles Targeted to the Endocardial Layer of the Injured Heart Modulate Hypertrophic Signaling. Issue 33 (17th July 2017) - Ferreira, Mónica P. A.; Ranjan, Sanjeev; Kinnunen, Sini; Correia, Alexandra; Talman, Virpi; Mäkilä, Ermei; Barrios‐Lopez, Brianda; Kemell, Marianna; Balasubramanian, Vimalkumar; Salonen, Jarno; Hirvonen, Jouni; Ruskoaho, Heikki; et al.
Abstract : Ischemic heart disease is the leading cause of death globally. Severe myocardial ischemia results in a massive loss of myocytes and acute myocardial infarction, the endocardium being the most vulnerable region. At present, current therapeutic lines only ameliorate modestly the quality of life of these patients. Here, an engineered nanocarrier is reported for targeted drug delivery into the endocardial layer of the left ventricle for cardiac repair. Biodegradable porous silicon (PSi) nanoparticles are functionalized with atrial natriuretic peptide (ANP), which is known to be expressed predominantly in the endocardium of the failing heart. The ANP–PSi nanoparticles exhibit improved colloidal stability and enhanced cellular interactions with cardiomyocytes and non‐myocytes with minimal toxicity. After confirmation of good retention of the radioisotope 111‐Indium in relevant physiological buffers over 4 h, in vivo single‐photon emission computed tomography (SPECT/CT) imaging and autoradiography demonstrate increased accumulation of ANP–PSi nanoparticles in the ischemic heart, particularly in the endocardial layer of the left ventricle. Moreover, ANP–PSi nanoparticles loaded with a novel cardioprotective small molecule attenuate hypertrophic signaling in the endocardium, demonstrating cardioprotective potential. These results provide unique insights into the development of nanotherapies targeted to the injured region of the myocardium. Abstract : Coronary heart disease is the main cause of death worldwide, the endocardium being the most vulnerable region for myocardial ischemia. Here, the development of a multifunctional nanoparticle with cardioprotective potential is reported, which selectively targets the endocardial layer of the left ventricle upon intravenous injection and delivers a drug molecule for modulating hypertrophic signaling.